Legal and Structural Basis for Regulation of Foreign Economic Relations in the Russian Federation Entities (Republic of Buryatia Case) - Asalkhanova, Sofya Alexeevna; Badmaeva, Irina Gennadyevna; Suliev, Vasiliy Fedoseyevich (International Journal of Economics and Financial Issues, 2015)
The article discusses the study on structural and legal framework for regulating foreign economic relations in the Russian Federation entities, and on the system of government bodies ensuring the development of foreign economic relations in the Republic of Buryatia. Russian Federation entities, in coordination with the Russian Ministry of Foreign Affairs, have the right to enter into agreements with foreign states and entities of foreign federal states, administrative and territorial units of foreign states, to establish their offices abroad, and to increase interest in having foreign state offices in the territory of Russia. Among the entities, the right to develop foreign economic relations is given to legislative and executive bodies - ministries, departments, committees and their structural units (managing departments, divisions) being built on the level of the entity of Russia. Specifically, the Ministry of Economic Affairs in the Republic of Buryatia is granted the power for implementing regional policy tasks in the sphere of international economic cooperation with the subjects of foreign states. Keywords: International economic cooperation, foreign economic relations, System of government JEL Classifications: F53; F59; R58